Factores de siembra en el rendimiento en peso de la caña de azúcar en la empresa Agroindustrial Casa Grande S.A.A. - Bueno Incil, Juan Alexander (2012)
This research present aims to determine the most influential factors in the yield in weight of sugarcane, by studying the many variables that influence this, such as nitrogen, age, number of cut, number of irrigation, soil type and variety of cane; done in the area of production and company laboratories, for which purpose the data in those variables corresponding to 30 fields of Empresa Agroindustrial Casa Grande SAA in 2008-2010._x000D_ Statistical analysis was performed in this research was the Multiple Linear Regression Model using the stepwise method, it was found that the model that explains the behavior of the variable yield (t/ha) is a function of age, the number of cut and variety of cane, with a coefficient of 0.821._x000D_ Subsequently went on to perform stock analysis influenciantes, observation detected 17 degrades the accuracy of the model and influences significantly the regression coefficients